Perancangan dan Pengembangan Sistem Pembelian Pre Order berbasis Website untuk Transaksi Jual Beli Produk Cabai - Muhammad Fadhil Hilmi; Hilmy Abidzar Tawakal (LPPM STT Terpadu Nurul Fikri, 2021)
The level of public consumption per capita of chili is relatively high. Chili needs in three sectors: households, industry, and hospitality (hotels, restaurants, and catering), increasing every year. However, general problems occur in the community every year, especially the fluctuations in chili prices which significantly affect inflation. This condition causes by the imbalance between supply and demand for chili. For this reason, Chilli Indonesia (Chili.id) designed an integrated agricultural business system specifically for chili commodities to meet the demand for chili. It starts from on-farm, off-farm, food processing to marketing using information technology (IT). Research writing provides a solution to the problems offered, namely by building a system that can accommodate chili demand for market needs. Pre-orders with website-based salam contracts make it easier for buyers to transact goods with certain conditions and provide farmers with the capital needed to grow chilies and secure chili stock needs for buyers. The development of the pre-order feature using the salam contract in this application uses the Agile Development Scrum method, which was developed based on the requirements or concepts in Chilli Indonesia or Chili.id.